Meaning of home and health dynamics among younger older people in Sweden - Kylén, Maya (Eur J Ageing, 2019)
Research has shown that positive evaluations of home are important for very old people’s health, well-being and independence in daily life. The rationale for the present study derives from our survey study findings, confirming such associations also in a younger cohort (N = 371). The purpose of this study was to further increase the understanding of the dynamics of meaning of home and health among community-living healthy younger older people, in the present and in a projected future. Data were collected through semi-structured interviews with 13 persons aged 67–70 years living in ordinary housing in Sweden, followed by a qualitative content analysis. Findings suggest that the home becomes progressively important after retirement. Not only the immediate home environment but also local neighbourhoods influence perceptions about home. Home brings emotional and social benefits but also worries about how to cope with complex home ambivalence when reflecting upon future housing arrangements. The findings suggest that it is important to consider the role of perceived aspects of home for health and well-being in early phases of the ageing process. The findings could be used to raise awareness among policymakers, housing authorities and professionals involved in housing-related counselling.